(untitled) (Research, Society and Development, 2022)
Objective: to identify the main factors associated with the incidence of femoral fractures in elderly patients. Methodology: descriptive, retrospective, documentary research with a quantitative approach, where the main factors associated with the occurrence of femur fractures in the elderly were explained during the period that patients were hospitalized in the medium and high complexity hospital from January 2018 to December 2019. Results: The female gender was predominant (59.4%), age group ≥80 years (43.6%), married (39.4%), elementary school (35.2%), retired (52, 7%), browns (92.7%), residents of Santarém (58.8%). The most frequent types of fractures and procedures were transtrochanteric fractures (53.3%) and osteosynthesis (72.1%), it was also observed that the most frequent comorbidity was hypertension (47.3%) and that most patients used some type of medication (53.9%). As for the causes of fractures, 22 types were found, the most prevalent being a fall from one’s own height (67.9%). Conclusion: It is concluded that the main factors found were falls from standing height, followed by falls due to other causes, with no statistical association between gender and age, type of fracture and causal factors, as well as causes with the use of medication or presence of comorbidities. However, there is a need to create programs that cover specific care for these elderly people in health institutions through qualified care with the aim of improving their quality of life.